Studi Literatur Tentang Program Pelatihan dan Pengembangan Kompetensi Sumber Daya Manusia di Era Digital - Nurulita, Aprilia; Bin Muhammad, Mutsanna (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to analyse the effectiveness of human resource training and development in improving competencies in the digital era. The research method used is descriptive through a literature study approach by reviewing several books, journal articles, and website sources relevant to the research topic. The results of this study show that training and development programmes are strategic steps in facing digital disruption. Along with the advancement of digital technology such as Artificial Intelligence (AI), Internet of Things (IoT), big data, data analytics, and business process automation, it is very helpful for companies in managing and developing human resources. HR training and development models in the digital era can be done through various methods such as e-learning, blended learing, and other platforms that make it easy for employees to improve their competence without being limited by time and place. The study results show that adaptive integration of digital technology in HR competency training can improve the efficiency and effectiveness of competency development in various organisational sectors.